2007
DOI: 10.1016/j.jns.2007.04.017
|View full text |Cite
|
Sign up to set email alerts
|

A decrease in N-acetylaspartate and an increase in myoinositol in the anterior cingulate gyrus are associated with behavioral and psychological symptoms in Alzheimer's disease

Abstract: We conclude that BPSD and the decline in cognitive function in AD might have separate pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…In a post-mortem magnetic resonance spectroscopy study, they found that AD patients with psychosis had greater neuropil disruption in multiple brain regions, including the dorsolateral prefrontal cortex, superior temporal gyrus and inferior parietal cortex. Similar accelerated biomarker changes have been shown in the anterior cingulate gyrus of AD patients with delusions compared to those without delusions [35]. The fact that AD patients with delusions had significantly worse functional performance in this study compared to those without delusions has implications for clinical care.…”
Section: Discussionsupporting
confidence: 82%
“…In a post-mortem magnetic resonance spectroscopy study, they found that AD patients with psychosis had greater neuropil disruption in multiple brain regions, including the dorsolateral prefrontal cortex, superior temporal gyrus and inferior parietal cortex. Similar accelerated biomarker changes have been shown in the anterior cingulate gyrus of AD patients with delusions compared to those without delusions [35]. The fact that AD patients with delusions had significantly worse functional performance in this study compared to those without delusions has implications for clinical care.…”
Section: Discussionsupporting
confidence: 82%
“…The authors concluded that this latter group (termed as asymptomatic AD) with marked neuronal hypertrophy (in the hippocampus, ACC, and PCC) might account for the functional compensation reflected in the different clinical outcome compared to mild cognitive impairment and AD subgroups. Interestingly, a recent 1 H-MRS study (Shinno et al 2007) found that an increase in NAA in the ACC might protect Alzheimer's disease patients from developing behavioral and psychological symptoms. The study demonstrated that the neuropsychological scores (on a fourpoint scale of increasing severity) obtained in two categories of BEHAVE-AD (delusional thought and activity disturbance) were negatively related to NAA/Cr in the ACC, but not in the posterior cingulate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…One can speculate that this greater disruption represents an acceleration of AD-related neurodegeneration. Proton magnetic resonance spectroscopy also allows the indirect measurement of AD pathology in living patients and has been used to implicate the anterior cingulate cortex (ACC) in patients with mild AD and delusions compared with those without delusions [32]. Delusional thinking was assessed in 30 AD patients using the BEHAVE-AD (Behavioral Pathology in Alzheimer's Disease) scale, and compared with AD-D patients (n=22), AD+D patients (n=8) had…”
Section: Neuropathologymentioning
confidence: 99%